2012
DOI: 10.1080/00028487.2012.688915
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neutrally Buoyant, Externally Attached Transmitters on Swimming Performance and Predator Avoidance of Juvenile Chinook Salmon

Abstract: Migrating juvenile salmonids experience rapid decompression that could result in injury or mortality due to barotrauma as they pass turbines at hydropower facilities. Recent research indicates that the risk of injury or mortality due to barotrauma is higher in fish bearing surgically implanted transmitters. Since tagged fish are used to represent the entire population, this tag effect potentially leads to inaccuracies in survival estimates for fish passing turbines. This problem led to development of a novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In a similar study of hatchery smolts, McCleave and Stred [66] found external tags to reduce the critical swimming speed in comparison with untagged control fish and intragastrically tagged fish. In a recent, comprehensive study by Janak et al [67] on hatchery-reared Chinook smolts, the mean Ucrit for control fish was 11 and 22 % higher than the mean for fish tagged with small and large external transmitters, respectively. For juvenile masu salmon (Oncorhynchus masou), the Ucrit of externally tagged fish was lower than that of surgically implanted and sham-tagged (surgical procedure without a tag inserted) groups [68].…”
Section: Swimming Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study of hatchery smolts, McCleave and Stred [66] found external tags to reduce the critical swimming speed in comparison with untagged control fish and intragastrically tagged fish. In a recent, comprehensive study by Janak et al [67] on hatchery-reared Chinook smolts, the mean Ucrit for control fish was 11 and 22 % higher than the mean for fish tagged with small and large external transmitters, respectively. For juvenile masu salmon (Oncorhynchus masou), the Ucrit of externally tagged fish was lower than that of surgically implanted and sham-tagged (surgical procedure without a tag inserted) groups [68].…”
Section: Swimming Performancementioning
confidence: 99%
“…Such effects may be reduced by dying the tag to blend with fish color, thus camouflaging the tag [67]. Bright tag labels with return-information should be kept on the side of the tag towards the fish to reduce the visibility.…”
Section: Social Interactionsmentioning
confidence: 99%
“…Additionally, externally attached tags have been shown to influence the hydrodynamics around the fish and can lead to decreased swimming performance and associated energy expenditure given increased frictional drag and flow resistance (Arnold and Holford, 1978;Ross and McCormick, 1981;Mellas and Haynes, 1985;Bridger and Booth, 2003;Jones et al, 2013;Janak et al, 2014). An increase in drag causes a proportional increase in power output of the tagged animal, described by:…”
Section: Tag Load Confounding Factorsmentioning
confidence: 99%
“…When evaluating swimming performance, juvenile Chinook salmon tagged with the neutrally buoyant external transmitters had a lower critical swimming speed ( Ucrit ) than untagged individuals. However, when compared to fish internally implanted with an acoustic transmitter and a passive integrated transponder (PIT) tag (a combined mass of 0.53 g), there was no significant difference in Ucrit [14]. Further, no mortalities or tag loss were observed during exposure to shear forces [7] and the presence of the tag did not increase the fish's susceptibility to barotrauma when compared to untagged fish [15].…”
Section: Introductionmentioning
confidence: 97%
“…Further research confirmed that the presence of the tag did not affect fish's performance compared to untagged individuals. For example, compared to untagged fish, there were no differences in growth or mortality over a 14-d holding period, or in predator avoidance [7], [14]. When evaluating swimming performance, juvenile Chinook salmon tagged with the neutrally buoyant external transmitters had a lower critical swimming speed ( Ucrit ) than untagged individuals.…”
Section: Introductionmentioning
confidence: 99%